2019
DOI: 10.1155/2019/1342762
|View full text |Cite
|
Sign up to set email alerts
|

HLA Polymorphisms and Haplotype Diversity in Transylvania, Romania

Abstract: Transylvania is a historical region in the northwestern part of Romanian with a rather heterogeneous population. Our study is the first to determine human leukocyte antigen (HLA) profiles in a large population sample from this region and to compare them with other European population groups. HLA genes were examined in 2,794 individuals using the Single Specific Primer-Polymerase Chain Reaction (SSP-PCR) and Polymerase Chain Reaction Sequence-Specific Oligonucleotide (PCR-SSO) methods. All samples were tested f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
3
4
0
Order By: Relevance
“…The most prevalent haplotype identified in both the severe and control groups was A*01~B*08~C*07~DRB1*03~DQB1*02 (Table 9). This haplotype aligns with the most frequently found haplotype in our previous study conducted on the population of Romanian origin in Transylvania [37]. To differentiate between the two groups more accurately, further studies employing high-resolution tests would be necessary.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The most prevalent haplotype identified in both the severe and control groups was A*01~B*08~C*07~DRB1*03~DQB1*02 (Table 9). This haplotype aligns with the most frequently found haplotype in our previous study conducted on the population of Romanian origin in Transylvania [37]. To differentiate between the two groups more accurately, further studies employing high-resolution tests would be necessary.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, the study was conducted on a cohort of 130 individuals of Romanian origin, the population for whom HLA association studies with COVID-19 had not been conducted before. Furthermore, there are few studies regarding the frequency of HLA alleles and haplotypes in the population of this region [36,37], and our previous studies have attempted to determine correlations between HLA alleles and certain infectious diseases or mental conditions in this population [10,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Research on the correlation of HLA profiles with autoimmune thyroid pathology is in an incipient phase, and extremely different and often contradictory results are being reported in studies conducted worldwide. Such discrepancies may be attributed to differences in allelic distribution among various populations [46], the generally small samples studied to date, and to the different methods employed in the research.…”
Section: Discussionmentioning
confidence: 99%
“…The different frequency of HLA alleles in various populations helps in both investigating the function of HLA genes and the genetic differentiation between individuals [42][43][44]. Some studies conducted in the population of Transylvania, Romania, revealed the frequency of HLA profiles and their association with some pathological conditions [45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the Transylvanian population, a study on 2,719 controls [37] analyzing the relative frequencies of HLA-DRB1 alleles found DRB1*11 (19%, n = 1033) to be the most frequent HLA-DRB1 allele, as was in Hungary, Greece, Serbia, Croatia, Slovakia, and Italy. Second most frequent were DRB1*03 and DRB1*13 (both 11.4%, n = 620), followed by DRB1*07 (10.6%, n = 576) and DRB1*16 The main limitation of our study consisted in the analysis of a Caucasian population of little ethnic variability from six Transylvanian counties and was also negatively impacted by the absence of a comprehensive HLA allele frequency database regarding Romanian patients with suicidal behavior, covering various ethnic subgroups from all regions of the country.…”
Section: Discussionmentioning
confidence: 99%